Ur III texts in the Schøyen collection - Dahl, Jacob L. (Manuscripts in the Schøyen Collection. Cuneiform texts, 2020)
Frontmatter -- Contents -- Statement of Provenance -- Series Editor’s Preface -- Preface -- Conventions -- Abbreviations -- Catalog -- Concordances -- 1. Introduction -- 2. Archival Documents -- 3. Timekeeping -- 4. Accounts -- 5. Equivalencies -- 6. Accountability -- 7. Receipts: The Primary Documents -- 8. Administration of Work -- 9. Letters -- 10. Messenger Texts. -- 11. Legal Texts -- 12. Miscellaneous Texts -- Appendix. Transliterations of Long Texts from Chapter 8: Worker Inventories -- References -- Indexes